NiO anode electrochromic film and preparation method and application thereof

By depositing an ultra-thin WO3 barrier layer in the NiO anode electrochromic film, the problem of NiO anode electrochromic materials producing high-valent nickel at high voltage is solved, and the device is highly cyclic stability and rapid response is achieved.

CN119667997APending Publication Date: 2025-03-21NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411863735.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the existing interlayer WO3-NiO electrochromic devices, NiO anode electrochromic materials are prone to produce high-valent nickel at high voltage, resulting in oxidation and decomposition reactions of the polymer electrolyte layer, causing device function failure.

Method used

Magneto-controlled sputtering technology is used to deposit NiO anode discoloration layer and ultra-thin WO3 barrier layer on the substrate surface in sequence to form a NiO anode electrochromic film. The thickness of the WO3 barrier layer is 10-40 nm, which prevents the direct contact between nickel oxide and polymer electrolyte, and improves the bonding strength and response speed through the high surface energy and ionic conductivity of WO3.

Benefits of technology

It effectively avoids the generation of bubbles during device operation, improves the cyclic stability and mechanical strength of the device, and improves the electrochemical cyclic stability and response speed of the NiO anode electrochromic film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119667997A_ABST
    Figure CN119667997A_ABST
Patent Text Reader

Abstract

The invention discloses a NiO anode electrochromic film and a preparation method and application thereof. The preparation method comprises the following steps: sequentially depositing a NiO anode color-changing layer and a WO3 barrier layer on the surface of a substrate by adopting a magnetron sputtering technology so as to obtain a NiO anode electrochromic film; wherein the thickness of the WO3 barrier layer is 10 to 40 nm. According to the interlayer type WO3-NiO electrochromic device, the NiO anode color changing layer is modified through WO3, the critical current density of the interlayer type WO3-NiO electrochromic device is improved, and the long cycle life can be achieved while the response speed of the device is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochromic materials and devices thereof, and in particular relates to a NiO anode electrochromic film and a preparation method and application thereof. Background Art

[0002] The electrochromic phenomenon refers to the electrochemical redox reaction of electrochromic materials under the action of an external electric field, the injection and extraction of ions and electrons in the electrochromic layer, which causes the optical properties of the material (reflectivity, transmittance, and absorptivity, etc.) to undergo stable and reversible changes. Since electrochromic devices have excellent adjustment capabilities in both visible and infrared bands, they have great application potential in smart windows for energy-saving buildings or skylight glass for electric vehicles.

[0003] Lamination technology is a low-cost, simple and commercially viable preparation method for large-area WO3-NiO electrochromic devices. The specific process involves: separately preparing glass / ITO / WO3 and glass / ITO / NiO components by magnetron sputtering coating, respectively as electrochromic electrodes (cathode) and ion storage electrodes (anode), and using special transparent polymers with high adhesion properties as intermediate electrolyte layers to form WO3-NiO devices by high-temperature vacuum lamination. Among them, polymer electrolyte is a key component of the above-mentioned sandwich WO3-NiO electrochromic device because it can dominate some key device performances, such as response time, cycle stability, optical properties, mechanical properties and thermal properties. The solid polymer electrolytes that have been developed include polymers based on polyvinyl butyral (PVB), polyethylene oxide (PEO), polymethyl methacrylate (PMMA) and polyacrylonitrile (PAN). Although much progress has been made in the research and development of sandwich WO3-NiO electrochromic devices, there are still some problems to be solved in the practical application process. Among them, the electrochemical damage of polymer electrolytes during operation is particularly prominent. This is because NiO will produce high-valent nickel (such as Ni) during the coloring process (especially at higher voltages). 4+ ), while the high price Ni 4+It has strong oxidizing properties, which leads to parasitic reactions of oxidation and decomposition at the interface of NiO and polymer electrolyte, producing gases such as CO2, CO and H2O, resulting in failure of the electrochromic function of the device. In order to solve the above problems, Electrochim.Acta.2018, 280:163-170 discloses a method for improving the cyclic stability of the device by covering the NiO surface with a 97nm thick Ta2O5 buffer layer. Studies have shown that the introduction of the Ta2O5 buffer layer can effectively alleviate the generation of bubbles during the operation of the device. However, facing the actual industrial application, this method still has the following shortcomings: Ta element is a rare and expensive element, and the Ta2O5 film layer is thick, resulting in a long sputtering time, increased material cost, and thus increased manufacturing cost of the device; Ta2O5 material has a low surface energy, and its water contact angle is usually greater than 75°. Such a low surface energy is not conducive to the good adhesion of solid polymer electrolytes on the film surface, and the bonding strength between the reaction electrode and the electrolyte is reduced, resulting in a decrease in the mechanical strength of the device such as impact resistance, and better application cannot be achieved. Therefore, there is an urgent need to find a material and means to improve the performance of NiO anode electrochromic materials in sandwich WO3-NiO electrochromic devices, further prevent the polymer electrolyte layer from being electrochemically damaged during device operation and improve various device performances. Summary of the invention

[0004] The main purpose of the present invention is to provide a NiO anode electrochromic film and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0006] An embodiment of the present invention provides a method for preparing a NiO anode electrochromic film, which comprises: using magnetron sputtering technology to sequentially deposit a NiO anode color-changing layer and a WO3 barrier layer on a substrate surface, thereby obtaining a NiO anode electrochromic film; wherein the thickness of the WO3 barrier layer is 10 to 40 nm.

[0007] The embodiment of the present invention also provides a NiO anode electrochromic film prepared by the aforementioned preparation method.

[0008] The embodiment of the present invention also provides the use of the aforementioned NiO anode electrochromic film in preparing an electrochromic device.

[0009] An embodiment of the present invention further provides an ion storage electrode, which includes the aforementioned NiO anode electrochromic film.

[0010] The embodiment of the present invention also provides a method for preparing a sandwich type WO3-NiO electrochromic device, which comprises:

[0011] The above-mentioned preparation method is used to prepare a NiO anode electrochromic film as an ion storage electrode; a transparent conductive oxide glass deposited with a WO3 cathode color-changing layer is used as an electrochromic electrode; a solid polymer electrolyte is used as an intermediate electrolyte layer;

[0012] Furthermore, the ion storage electrode, the intermediate electrolyte layer and the electrochromic electrode are assembled by vacuum lamination to obtain a sandwich type WO3-NiO electrochromic device.

[0013] The embodiment of the present invention also provides a sandwich type WO3-NiO electrochromic device prepared by the aforementioned preparation method.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] (1) WO3 used in the present invention is a commonly used material in the preparation process of electrochromic devices, and the material is easy to obtain and has low cost;

[0016] (2) The present invention forms an ultra-thin (<40 nm) WO3 barrier layer to prevent direct contact between nickel oxide and the polymer electrolyte, thereby preventing bubbles from being generated during device operation;

[0017] (3) WO3 in the present invention has a higher surface energy, which improves the bonding strength between the polymer electrolyte and the NiO anode electrochromic film;

[0018] (4) WO3 in the present invention has a higher ionic conductivity, which reduces Li + The transmission impedance increases the response speed of the NiO anode electrochromic film;

[0019] (5) The present invention utilizes W atoms in the WO3 sputtering process to bombard the NiO anode color-changing layer, which can eliminate defects inside the film (such as micropores, loose structures, etc.), improve the structural stability of the film, reduce surface roughness, and also help to achieve W doping, ultimately improving the electrochemical cycle stability of the NiO anode electrochromic film;

[0020] (6) The present invention improves the critical current density (CCD) of the sandwich WO3-NiO electrochromic device by modifying the surface of the NiO anode color-changing layer with WO3, which is conducive to achieving a high device response speed while achieving a long cycle life;

[0021] (7) The present invention utilizes amorphous WO3 in Li + The huge change in resistivity during the intercalation / deintercalation process creates a uniform electric field, thereby achieving uniform coloring or fading of large-area devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1a is a SEM photo of Comparative Example 1 of the present invention, Figure 1b is a SEM photograph of Example 1 of the present invention;

[0024] Figure 2a-2b They are respectively the water contact angle diagrams of the film surfaces of Comparative Example 1 and Example 1 of the present invention;

[0025] Figure 3a This is a TEM photo of Comparative Example 1 of the present invention, Figure 3b This is a TEM photo of Example 1 of the present invention;

[0026] Figure 4 is the EDS spectrum of the sample prepared in Example 1 of the present invention;

[0027] Figure 5a-Figure 5b They are the color fading transmittance spectrum and appearance diagram of the film prepared in Comparative Example 1 and Example 1 of the present invention respectively;

[0028] Figure 6a-6b Electrochemical cyclic voltammetry (CV) diagrams of the samples of Comparative Example 1 and Example 1 of the present invention run at a scan rate of 50 mV / s in the range of -1.0 V to 1.5 V;

[0029] Figure 7 The optical transmittance variation curves of the films of Comparative Example 1 and Example 1 of the present invention at 550nm are shown;

[0030] Figure 8 This is a curve diagram of optical transmittance variation at 550nm for Comparative Example 3 of the present invention;

[0031] Fig. 9 It is a critical current density test diagram of Comparative Example 2 and Example 2 of the present invention;

[0032] Fig.10 Figures before and after the cycles of Comparative Example 2 and Example 2 of the present invention;

[0033] Figure 11a-Figure 11c The transmittance (550nm) diagrams and corresponding appearance photos of nine different areas in different colored and faded states of Comparative Example 2 and Example 2 of the present invention. DETAILED DESCRIPTION

[0034] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a NiO anode electrochromic film involves: using magnetron sputtering technology to sequentially deposit a NiO anode color-changing layer and a WO3 barrier layer on the surface of a substrate, thereby obtaining a NiO anode electrochromic film; wherein the thickness of the WO3 barrier layer is 10 to 40 nm.

[0036] In some preferred embodiments, the preparation method specifically comprises: using magnetron sputtering technology, using an inert gas as a working gas, using a WO3 ceramic body as a target material, depositing a WO3 barrier layer on the surface of a substrate on which a NiO anode color-changing layer is deposited, thereby obtaining a NiO anode electrochromic film; wherein the background vacuum of the sputtering chamber is 5×10 -2 -5×10 -4 Pa, the working gas pressure is 0.6-2.0Pa, and the sputtering power density is 2.2-5.5W / cm 2 .

[0037] In some preferred embodiments, the NiO anode color-changing layer includes a NiO layer and / or a doped NiO layer; wherein the doped NiO layer includes a NiO layer doped with any one or more elements of W, Si, Zn, Zr, and Li.

[0038] In some preferred embodiments, the substrate includes transparent conductive oxide glass, and the transparent conductive oxide glass includes any one of ITO glass, FTO glass, and AZO glass, but is not limited thereto.

[0039] Another aspect of the embodiments of the present invention further provides a NiO anode electrochromic film prepared by the aforementioned preparation method.

[0040] Another aspect of the embodiments of the present invention further provides use of the aforementioned NiO anode electrochromic film in preparing an electrochromic device.

[0041] Another aspect of an embodiment of the present invention further provides an ion storage electrode, which includes the aforementioned NiO anode electrochromic film.

[0042] Another aspect of the embodiments of the present invention further provides a method for preparing a sandwich WO3-NiO electrochromic device, which comprises:

[0043] The above-mentioned preparation method is used to prepare a NiO anode electrochromic film as an ion storage electrode; a transparent conductive oxide glass deposited with a WO3 cathode color-changing layer is used as an electrochromic electrode; a solid polymer electrolyte is used as an intermediate electrolyte layer;

[0044] Furthermore, the ion storage electrode, the intermediate electrolyte layer and the electrochromic electrode are assembled by vacuum lamination to obtain a sandwich type WO3-NiO electrochromic device.

[0045] In some preferred embodiments, the WO3 cathode color-changing layer includes a WO3 layer and / or a doped WO3 layer; wherein the doped WO3 layer includes a WO3 layer doped with any one or more elements of Nb, V, and Mo.

[0046] In some preferred embodiments, the solid polymer electrolyte includes an electrolyte containing a lithium salt based on any one or more polymer combinations of polyvinyl butyral, polyethylene oxide, polymethyl methacrylate, and polyacrylonitrile.

[0047] In some preferred embodiments, the transparent conductive oxide glass includes any one of ITO glass, FTO glass, and AZO glass, but is not limited thereto.

[0048] In some more specific embodiments, the method for preparing the sandwich type WO3-NiO electrochromic device comprises:

[0049] The NiO anode color-changing layer deposited on the transparent conductive oxide glass, which is self-made or purchased, is placed in the magnetron sputtering coating chamber. The WO3 ceramic body is used as the target material. The magnetron sputtering method is used to deposit a WO3 barrier layer with a thickness of 10 to 40 nm. The sputtering process parameters are: pure Ar is used as the working gas, and the background vacuum of the sputtering chamber is 5×10 -2 -5×10 -4 Pa, the working pressure is 0.6-2.0Pa, and the sputtering power density is 2.2-5.5W / cm 2 , the substrate is heated unintentionally;

[0050] Then, a sandwich WO3-NiO electrochromic device is prepared by conventional vacuum lamination process using a homemade or purchased WO3 cathode color-changing layer deposited on a transparent conductive oxide glass as the main color-changing layer and a homemade or purchased solid polymer electrolyte.

[0051] Furthermore, the transparent conductive oxide includes ITO, FTO, AZO and the like.

[0052] Furthermore, the NiO anode color-changing layer includes: pure NiO, and NiO doped with a single element or multiple elements such as W, Si, Zn, Zr, and Li.

[0053] Furthermore, the WO3 cathode color-changing layer includes: pure WO3, and WO3 doped with elements such as Nb, V, and Mo.

[0054] Furthermore, the solid polymer electrolyte includes: an electrolyte containing lithium salt based on polymers such as polyvinyl butyral (PVB), polyethylene oxide (PEO), polymethyl methacrylate (PMMA) and polyacrylonitrile (PAN).

[0055] Another aspect of the embodiments of the present invention further provides a sandwich WO3-NiO electrochromic device prepared by the aforementioned preparation method.

[0056] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0057] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0058] Comparative Example 1:

[0059] Referring to the process parameters of step 1 of Example 4 in the patent application number CN202011462486.2, a Li and Si co-doped NiO film with a thickness of 114 nm was deposited on an ITO glass substrate.

[0060] Comparative Example 2:

[0061] The NiO film prepared in comparative example 1 is used as the anode color-changing film, and the process parameters of Example 2 in the patent with reference application number CN202311659486.5 are used to deposit a Nb-doped WO3 film with a thickness of 350nm on an ITO glass substrate as a cathode color-changing film, and the PVB-based polymer prepared in Example 1 in the patent with application number CN202310063503.2 is used as the electrolyte, and then the WO3-NiO electrochromic device is prepared by a lamination process, and the lamination conditions are: temperature 130°C, time 2h, and pressure 1.5MPa.

[0062] Comparative Example 3

[0063] The NiO anode color-changing film prepared in Comparative Example 1 was used as the substrate material and placed in a magnetron sputtering coating chamber. The WO3 ceramic body was used as the target material. The magnetron sputtering method was used to deposit a WO3 film with a thickness of 55am. The sputtering process parameters were: pure Ar was used as the working gas, and the background vacuum of the sputtering chamber was 5×10 -4 Pa, the working gas pressure is 2.0Pa, and the sputtering power density is 5.5W / cm 2 , the substrate was not intentionally heated to obtain a NiO anode electrochromic film. A 350nm thick Nb-doped WO3 film was deposited on an ITO glass substrate as a cathode color-changing film using the process parameters of Example 2 in the patent with reference to application number CN202311659486.5, and a PVB-based polymer prepared in Example 1 in the patent with application number CN202310063503.2 was used as an electrolyte. Then, a lamination process was used to prepare a WO3-NiO electrochromic device. The lamination conditions were: temperature 130°C, time 2h, and pressure 1.5MPa.

[0064] Example 1

[0065] The NiO anode color-changing film prepared in Comparative Example 1 was used as the substrate material and placed in a magnetron sputtering coating chamber. The WO3 ceramic body was used as the target material. The magnetron sputtering method was used to deposit a WO3 film with a thickness of 30am. The sputtering process parameters were: pure Ar was used as the working gas, the background vacuum of the chamber was 5×10 -4 Pa, the working gas pressure is 2.0Pa, and the sputtering power density is 5.5W / cm 2 , the substrate is not heated intentionally.

[0066] Example 2

[0067] The NiO film prepared in Example 1 is used as the anode color-changing film, and the Nb-doped WO3 film with a thickness of 350nm deposited on the ITO glass substrate according to the process parameters of Example 2 in the patent with application number CN202311659486.5 is used as the cathode color-changing film. The PVB-based polymer prepared in Example 1 published in the patent with application number CN202310063503.2 is used as the electrolyte, and then the WO3-NiO electrochromic device is prepared by a lamination process. The lamination conditions are: temperature 130°C, time 2h, and pressure 1.5MPa.

[0068] Performance characterization:

[0069] The surface morphology of the film was observed by scanning electron microscopy (SEM), the water contact angle on the film surface was observed by water contact angle meter, the microstructure and morphology of the film was observed by transmission electron microscopy (TEM), the composition and distribution of elements were observed by energy dispersive X-ray spectrometer (EDS), the optical modulation amplitude and electrochromic response time of the film were measured by UV-visible spectrophotometer, and the electrochemical properties, cycle stability and other electrochromic properties of the film were measured by electrochemical workstation.

[0070] Figure 1a This is the SEM photo of Comparative Example 1. Figure 1b The SEM photo of Example 1 is given. As can be seen from the figure, the surface of Comparative Example 1 is rough, with large semi-embedded particles and large surface roughness, but after depositing WO3, the film becomes smooth and dense. This indicates that during the sputtering of WO3, the sputtered W atoms will bombard the surface of the substrate film and remove the protruding structure.

[0071] Figure 2a and Figure 2b They are respectively the water contact angle diagrams of the film surfaces of comparative example 1 and embodiment 1. It can be seen from the figure that the water contact angle of embodiment 1 is reduced to 10° compared with 75° of comparative example 1, indicating that the surface energy of embodiment 1 is high, which is conducive to the bonding between the reaction electrode and the electrolyte and improves the cycle life of the device.

[0072] Figure 3a This is the TEM photo of Comparative Example 1. Figure 3b The TEM photo of Example 1 is given. In Comparative Example 1, the NiO film grows in a columnar shape, the film surface is relatively rough, the average grain diameter is 12.9 nm, and there are a large number of embedded defects (such as micropores and highly loose microstructures, marked with circles). In Example 1, the NiO layer still maintains columnar growth after WO3 deposition, and the average grain size is reduced to 10.1 nm; more importantly, a compact microstructure and a high surface flatness can be observed.

[0073] Figure 4 This is the EDS spectrum of the sample prepared in Example 1 of the present invention. It can be seen that a uniform distribution of W element is detected inside NiO, and a strong distribution of W element appears in a narrow area (about 10 nm) on the surface of the NiO layer. This shows that during the sputtering process of WO3, the sputtered W atoms will penetrate into the interior of the NiO layer to achieve uniform W doping.

[0074] Figure 5a and Figure 5b The fading transmittance spectrum and appearance of the film prepared in Comparative Example 1 and Example 1 are shown respectively. It can be seen from the figure that although Example 1 has a lower modulation amplitude (ΔT, fading transmittance (Tb) and colored transmittance (T c) decreased slightly (from 44.7% to 37.5%), but the transmittance of Example 1 in the faded state was higher. The sample appearance was consistent with the transmittance spectrum, and Example 1 showed a clearer, almost colorless appearance in the faded state. This shows that the thickness of the WO3 modified layer is appropriate and will not cause coloration of the WO3 itself during the fading process of lithium ion insertion.

[0075] Figure 6a and Figure 6b The electrochemical cyclic voltammetry (CV) diagram of the samples of Comparative Example 1 and Example 1 was run at a scan rate of 50 mV / s in the range of -1.0 V to 1.5 V. It can be seen from the figure that the charge capacity of Comparative Example 1 increased from 20.4 mC cm in the third CV cycle to -2 It dropped to 5.7 mC cm at the 100th CV cycle. -2 However, the surface modification of WO3 makes the electrochemical cycle of the sample in Example 1 more stable, and the charge capacity is almost unchanged (18.4 mC cm at the third CV cycle). -2 , the 100th CV cycle is 19.1 mC cm -2 ). This shows that the WO3 modification on the surface of NiO film can improve the cycle stability of the film.

[0076] Figure 7 The optical transmittance change curves of the films of Comparative Example 1 and Example 1 at 550nm, with 1V and -1V voltages applied for 60s. The response time usually refers to the time when the coloring state reaches 90% when the coloring state is completely faded. As can be seen from the figure, the coloring time (tc) of Example 1 is 16s, which is shorter than the 23s of Comparative Example 1, and the fading time (tb) of Example 1 is 2s, which is also shorter than the 3s of Comparative Example 1. This result shows that the surface modification of WO3 increases the shuttle speed of lithium ions during the coloring or fading process.

[0077] Figure 8 The optical transmittance change curve of the device of comparative example 3 at 550nm, with -2.5V and 1.5V voltages applied for 60s. It can be seen from the figure that when the device is in the colored state, the voltage of -2.5V is continued to be maintained, and the device begins to fade; when the voltage of -2.5V is continued to be maintained in the faded state, the device begins to color; this shows that the thicker WO3 modified layer on the NiO surface has a more significant color change reaction when a voltage is applied.

[0078] Fig. 9 The critical current density test diagrams of Comparative Example 2 and Example 2 are shown. The electrochromic critical current density (CCD) was detected by operating at different positive / negative current densities for 5 s and cycling for more than 200 times. For Comparative Example 2, the critical current density of 0.05 and 0.15 mA cm -2The potential remains stable during the switching process, but when the current density increases to 0.25 mA cm -2 When the potential rises sharply, it is because bubbles are generated at the interface between the active layer and the electrolyte layer, which hinders the movement of ions and increases the impedance. The critical current density of comparative example 2 can be regarded as 0.15 mA cm -2 After surface modification of WO3, the critical current density of Example 2 was significantly increased to 0.45 mA cm- 2 , which is three times that of the unmodified device. This shows that WO3 surface modification reduces the impedance of ion shuttling during the electrochromic reaction, and only a smaller voltage is needed to activate the device.

[0079] Fig.10 The following are the appearance photos of Comparative Example 2 and Example 2 before and after the cycles. Obviously, after a small number of electrochemical cycles, Comparative Example 2 produces a large number of small bubbles (marked with circles) near the electrode, while Example 2 remains unchanged. It can be inferred that the reason for the generation of bubbles is the strong oxidation side reaction of high-valent (Ni>3+) nickel, and WO3 surface modification can effectively prevent the generation of such reactions.

[0080] Figure 11a-Figure 11c The area of ​​the comparative example 2 and the example 2 under different coloring and fading states is 100 cm 2 The transmittance (550nm) graph of the sample in nine different areas and the corresponding appearance photos. It can be seen that the device fades evenly during operation, and the maximum transmittance deviation (T Max -T Min ) is 6.3%. This result shows that WO3 surface modification has great application potential in achieving uniform coloring of larger size devices. Studies have shown that amorphous WO3 can significantly enhance its conductive properties after inserting a small amount of lithium ions, with the resistivity increasing from 2×10 7 Reduced to 4×10 2 Ω·cm, which will form a uniform electric field on the color-changing layer electrode, thereby further ensuring a high degree of uniformity in coloring.

[0081] Example 3

[0082] The NiO anode color-changing film prepared in Comparative Example 1 was used as the substrate material and placed in a magnetron sputtering coating chamber. The WO3 ceramic body was used as the target material. The WO3 film with a thickness of 10 nm was deposited by magnetron sputtering. The sputtering process parameters were: pure Ar was used as the working gas, the background vacuum of the chamber was 5×10 -4 Pa, the working pressure is 0.6Pa, and the sputtering power density is 5.5W / cm 2 , the substrate is not heated intentionally.

[0083] Example 4

[0084] The NiO anode color-changing film prepared in Comparative Example 1 was used as the substrate material and placed in a magnetron sputtering coating chamber. The WO3 ceramic body was used as the target material. The WO3 film with a thickness of 40 nm was deposited by magnetron sputtering. The sputtering process parameters were: pure Ar was used as the working gas, the background vacuum of the chamber was 5×10 -4 Pa, the working pressure is 2.0Pa, and the sputtering power density is 2.2W / cm 2 , the substrate is not heated intentionally.

[0085] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0086] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a NiO anode electrochromic film, characterized in that: include: A NiO anode electrochromic layer and a WO3 barrier layer are sequentially deposited on the substrate surface by magnetron sputtering technology, thereby obtaining a NiO anode electrochromic film; wherein the thickness of the WO3 barrier layer is 10N40nm.

2. The preparation method according to claim 1, characterized in that: Specifically include: The magnetron sputtering technology was used, with inert gas as the working gas and WO3 ceramic as the target material, to deposit a WO3 barrier layer on the surface of the substrate with the NiO anode color-changing layer deposited, thereby obtaining the NiO anode electrochromic film; wherein, the background vacuum degree of the sputtering chamber was 5×10 -2 -5×10 -4 Pa, the working gas pressure is 0.6-2.0Pa, and the sputtering power density is 2.2-5.5W / cm 2 .

3. The preparation method according to claim 1, characterized in that: The NiO anode color-changing layer includes a NiO layer and / or a doped NiO layer; wherein the doped NiO layer includes a NiO layer doped with any one or more elements of W, Si, Zn, Zr, and Li.

4. The preparation method according to claim 1, characterized in that: The substrate includes transparent conductive oxide glass, and the transparent conductive oxide glass includes any one of ITO glass, FTO glass, and AZO glass.

5. A NiO anode electrochromic film prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the NiO anode electrochromic film according to claim 5 in the preparation of electrochromic devices.

7. An ion storage electrode, characterized in that It includes the NiO anode electrochromic film as described in claim 5.

8. A method for preparing a sandwich WO3-NiO electrochromic device, characterized in that: include: A NiO anode electrochromic film is prepared by the preparation method according to any one of claims 1 to 4 as an ion storage electrode; A transparent conductive oxide glass with a WO3 cathode color-changing layer deposited thereon is used as an electrochromic electrode; a solid polymer electrolyte is used as an intermediate electrolyte layer; Furthermore, the ion storage electrode, the intermediate electrolyte layer and the electrochromic electrode are assembled by vacuum lamination to obtain a sandwich type WO3-NiO electrochromic device.

9. The preparation method according to claim 8, characterized in that: The WO3 cathode color-changing layer includes a WO3 layer and / or a doped WO3 layer; wherein the doped WO3 layer includes a WO3 layer doped with any one or more elements of Nb, V, and Mo; And / or, the solid polymer electrolyte comprises an electrolyte containing lithium salt based on any one or more polymer combinations of polyvinyl butyral, polyethylene oxide, polymethyl methacrylate, and polyacrylonitrile; And / or, the transparent conductive oxide glass includes any one of ITO glass, FTO glass, and AZO glass.

10. A sandwich WO3-NiO electrochromic device prepared by the preparation method according to claim 8 or 9.

Citation Information

Patent Citations

  • Multifunctional dimming device and laminated glass, hollow glass and attached film thereof

    CN113867017A

  • Electrochromism element

    CN1510494A

  • Electrochromic device comprising tandem layers of cathodic / anodic materials

    US6211995B1